Sequential treatments in hereditary leiomyomatosis and renal cell carcinoma (HLRCC): Case report and review of the literature - de Velasco, Guillermo; Munoz, Cesar; Sepulveda, Juan M.; Castellano, Daniel (Canadian Urological Association Journal, 2015)
The overall survival for patients with advanced papillary renal carcinoma (RCC) is still limited. Although multikinase inhibitors have recently been developed for clear cell carcinoma, response rates in other histology non-clear cell RCC are poor and patients often face dose-limiting toxicities which lead to a reduction in prognosis and treatment success. We present a patient with hereditary leiomyomatosis and RCC (HLRCC), showing a sustained response for more than 12 months to gemcitabine-bevacizumab therapy after failure tyrosine kinase inhibitors (TKIs) and mammalian target of rapamycin (mTOR) therapies.